An adoption clinic: protection and care context in family therapy - Bambini Vasconcellos, Maria Luiza (2023)
This text seeks to highlight how adoption – in its paths and specificities – can peculiarly benefit from Family Therapy. However, it may be regarded as an essay, due to its registration character for a clinic under construction, either by the recent history of operation in this capacity in our country so it can be demanded as such, or by calling an existing theoretical universe upon itself, at the same time it unveils new views and concepts to be recognized in its legitimacy and competence. Under such conditions, some aspects were chosen among uncountable ones that come and go within the lives of those who adopt and those who are adopted – as many as could be present in the subjectivity of each subject going through this experience – for the fact they enlighten the reflections presented here, although they do not claim to contemplate the complexity of these experiences, nor to represent them. It is, therefore, a question of delineating a field in which therapeutic work takes place in an inclusive way, through a work that is based on dialogue, on the recognition of the relevance of all those involved and in the commitment of the power of desire in the feasibility and co-creation of new family configurations.